THE ROLE OF VITAMIN D, VITAMIN D RECEPTOR GENE FOKI POLYMORPHISM, AND CATHELICIDIN IN TUBERCULOSIS INFECTION IN CHILDREN - AMELIN, FITRISIA; YANI, FINNY FITRI; MACHMUD, RIZANDA (International Journal of Applied Pharmaceutics, 2019)
Objective: Recent studies have reported that vitamin D has an important role in tuberculosis. Polymorphism of single nucleotide polymorphism (SNP) rs2228570 or FokI will generate proteins with various amino acid lengths, and affect the molecular physiological roles of vitamin D. Cathelicidin acts as an antimicrobial directly against Mycobacterium tuberculosis (Mtb) and mediator autophagy by macrophages induced by vitamin D. This study aims to determine the role of vitamin D, vitamin D receptor gene SNP rs2228570 (FokI), and plasma levels of cathelicidin in children with tuberculosis infection. Methods: This cross-sectional was conducted on children aged £14 y who had close contacts with an adult who had sputum smear positive for acid-fast bacilli indicating pulmonary TB. The children were divided into two groups: those with and those without TB infection. Demographic data and blood samples were taken from children participating in this study to examine polymorphisms and cathelicidin plasma levels, and to determine the association between these levels in children with and without TB infection. Results: There were no differences in the proportion of genotype and allele of SNP rs2228570 vitamin D receptor gene (FokI), polymorphisms of VDR, and cathelicidin plasma levels between children with and without TB infection (p>0.05). However, nutritional status and levels of cathelicidin by age category increased the risk of TB infection (p<0.05). Conclusion: Cathelicidin level in children with TB infection lower than without. Vitamin D and FokI polymorphism did not play role in TB infection.